Wish you were here A Novel - Picoult, Jodi; Picoult, Jodi (Great Britain Hodder & Stoughton, 2021)
Wish You Were Here (2021) is a novel by Jodi Picoult, which, according to the author, is about (3z(Bthe resilience of the human spirit in a moment of crisis.(3y (BThe story follows a young woman, Diana O$1 (BToole, who leaves for a vacation to the Galapagos without her boyfriend and gets locked down there as borders close under quarantine during the Covid-19 pandemic. Away from everything and everyone familiar, Diana must adapt to these extraordinary circumstances through a journey of self-reflection, awareness, and connection.s
English
Keywords: Picoult, Jodi